Met die oog op genesingsdienste in die Nederduitse Gereformeerde Kerk - Theron, J. P. J. (Verbum et ecclesia, 1991)
Towards healing services in the Dutch Reformed Church The position of the Dutch Reformed Church in South Africa with regard to the world wide recovery of the Church’s healing ministry is discussed. Features of liturgical healing services of other denominational churches are utilised to develop a model for the Dutch Reformed Church in Initiating this kind of public ministry.